Assessing the Utility of a Quality-of-Care Assessment Tool Used in Assessing Comprehensive Care Services Provided by Community Health Workers in South Africa - Babalola, Olukemi; Goudge, Jane; Levin, Jonathan; Brown, Celia; Griffiths, Frances (Frontiers in Public Health, 2022)
Background Few studies exist on the tools for assessing quality-of-care of community health worker (CHW) who provide comprehensive care, and for available tools, evidence on the utility is scanty. We aimed to assess the utility components of a previously-reported quality-of-care assessment tool developed for summative assessment in South Africa. Methods In two provinces, we used ratings by 21 CHWs and 3 team leaders in two primary health care facilities per province regarding whether the tool covered everything that happens during their household visits and whether they were happy to be assessed using the tool (acceptability and face validity), to derive agreement index (≥85%, otherwise the tool had to be revised). A panel of six experts quantitatively validated 11 items of the tool (content validity). Content validity index (CVI), of individual items (I-CVI) or entire scale (S-CVI), should be >80% (excellent). For the inter-rater reliability (IRR), we determined agreement between paired observers’ assigned quality-of-care messages and communication scores during 18 CHW household visits (nine households per site). Bland and Altman plots and multilevel model analysis, for clustered data, were used to assess IRR. Results In all four CHW and team leader sites, agreement index was ≥85%, except for whether they were happy to be assessed using the tool, where it was <85% in one facility. The I-CVI of the 11 items in the tool ranged between 0.83 and 1.00. For the S-CVI, all six experts agreed on relevancy (universal agreement) in 8 of 11 items (0.72) whereas the average of I-CVIs, was 0.95. The Bland-Altman plot limit of agreements between paired observes were -0.18 to 0.44 and -0.30 to 0.44 (messages score); and -0.22 to 0.45 and -0.28 to 0.40 (communication score). Multilevel modelling revealed an estimated reliability of 0.77 (messages score) and 0.14 (communication score). Conclusion The quality-of-care assessment tool has a high face and content validity. IRR was substantial for quality-of-care messages but not for communication score. This suggests that the tool may only be useful in the formative assessment of CHWs. Such assessment can provide the basis for reflection and discussion on CHW performance and lead to change.